Granulomatous‐lymphocytic interstitial lung disease as the first manifestation of common variable immunodeficiency. (22nd June 2016) - Tashtoush, Basheer; Memarpour, Roya; Ramirez, Jose; Bejarano, Pablo; Mehta, Jinesh
Abstract: Common variable immunodeficiency (CVID) is one of the most common primary immunodeficiencies, which is characterized by reduced serum immunoglobulin levels and B‐lymphocyte dysfunction. There are many clinical manifestations of this disease, the most common of which are recurrent respiratory tract infections. Among the most recently recognized autoimmune manifestation of CVID is a disease described as granulomatous‐lymphocytic interstitial lung disease (GLILD), where CVID coexists with a small airway lymphoproliferative disorder, mimicking follicular bronchiolitis, or lymphocytic interstitial pneumonitis (LIP) on histology specimens. We herein describe the clinical and radiological features of GLILD in a 55‐year‐old woman where the diagnosis of CVID was actively pursued and eventually confirmed after her lung biopsy showed characteristic features of GLILD. The patient had dramatic response to treatment with IVIG and corticosteroids for 3 months followed by Mycophenolate mofetil for maintenance therapy.